Protein Lipidation by Palmitoylation and Myristoylation in Cancer - Fhu, Chee Wai; Ali, Azhar (Frontiers in Cell and Developmental Biology, 2021)
Post translational modification of proteins with lipid moieties is known as protein lipidation. Attachment of lipid molecule to proteins endows distinct properties which affect their hydrophobicity, structural stability, localization, trafficking between membrane compartments and influences its interaction with effectors. Lipids or lipid metabolites can serve as substrates for lipidation and the availability of these lipid substrates are tightly regulated by cellular metabolism. Palmitoylation and myristoylation represent the two most common protein lipid modifications and dysregulation of protein lipidation is strongly linked to various diseases such as metabolic syndromes and cancers. In this review, we present recent developments in our understanding on the roles of palmitoylation and myristoylation, and their significance in modulating protein function and cellular signaling towards cancer initiation and progression.